Hukum Zina Dalam Islam:Perspektif Moral - amrudin; Habibi. H; Nur Afifa Maharani (CV. ITTC INDONESIA, 2025)
This article examines the law of adultery (zina) in Islam from a moral perspective, viewing it not merely as a criminal offense in Islamic law (jināyah), but also as a form of ethical, spiritual, and social degradation. The study aims to analyze the Islamic concept of adultery, its classification into zinā ḥaqīqī and zinā majāzī, and its moral and social implications. This research employs a library research method with a descriptive-analytical and normative approach, utilizing primary sources such as the Qur’an, Hadith, classical Islamic scholars’ opinions, and Indonesian positive law. The findings indicate that the prohibition of adultery in Islam contains a strong preventive moral dimension intended to protect human dignity, natural disposition (fiṭrah), lineage (ḥifẓ al-nasl), and social order. Legal sanctions, both in Islamic law and Indonesian criminal law, function not only as repressive measures but also as educational and preventive instruments. Therefore, the prevention of adultery should primarily be grounded in moral strengthening and spiritual awareness rather than relying solely on legal punishment.